Molecular interaction of carboxylic and amine group with calcium and iron for solid scale dissolution - M. H., Sulaiman; Fatmawati, Adam; Z., M. Noor (2018)
Calcium carbonate is one of the common solid scale in oil and gas upstream production occurred along with other type of scale such as iron (II) sulphide. Commonly, acid is used for dissolution of solid scale however acid is corrosive and dangerous to handle [1]. Non-acidic dissolution technology such as chelating agent form complexes with metals ions and highly depends on pH [2]. The agent may contain carboxylic and amine as the main functional group that plays a role in solid scale dissolution. This paper aims to study the molecular interaction between carboxylic and amine group with metal ions in calcium carbonate (CaCO3) and iron (II) sulphide (FeS).